Hyperbaric oxygen therapy for carbon monoxide poisoning - Verda Tuna; Kesici Sevgi; Selma Ozkan; Gulgun Elif Akcali; Ebubekir Esen; Ozkan Orhan (CHRISMED Journal of Health and Research, 2014)
Carbon monoxide poisoning is a life-threatening poisoning. In this case report neurological findings developed in carbon monoxide poisoning and the importance of multidisciplinary approach are discussed. The patient, 16-year-old male, was found unconscious following a 1-hour exposure to gas water heater poisoning and brought to our hospital after being intubated at the scene of the accident. After treatment for bicarbonate deficit, hepatamine infusion was started and hyperbaric oxygen treatment was performed. The patient was connected to mechanical ventilator in our department. The treatment were performed for cerebral edema. And hyperbaric oxygen treatment continued for 12 days. The patient was disconnected from the ventilator on the 36 th day of the follow-up. Medical history and clinical examination are very important in the diagnosis of carbon monoxide poisoning. The patient should be followed up with laboratory examinations and imaging methods such as magnetic resonance imaging in order not to overlook neurological sequelae or any organ injury. Additionally hyperbaric oxygen treatment performed in acute period and goal-directed therapy decrease mortality and morbidity.